Multiple Traits-based Analysis of Tartary Buckwheat Landraces Using GGE-Biplot - Joshi, Bal K (Nepal Journal of Science and Technology, 2013)
Selection of landraces using multiple traits can be considered more effective in crop breeding program. The objective was to enhance the yield performance of landraces of Tartary buckwheat through pure line selection method. Seven landraces were selected from the evaluation trials of 105 accessions in 2007 and 2008 based on the grain yield per plant and analyzed by genotype by trait (GT) biplot using seven quantitative traits: plant height, grain yield, number of leaves, number of grains, days to maturity, 500-grain weight and number of primary branches. The landrace, Ghyuri was found to be the best landrace based on the multiple traits analysis and it produced the highest grain yield (5.36 g per plant) and had the highest number of grains (276). The weight of 500-grain was the lowest (8.08 g) in check variety, i.e., Kabre Tite. Ghyuri followed by MY-2-33-1 had higher values for all these traits, where as Kabre Tite had below average values for all traits. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 1-6 DOI: http://dx.doi.org/10.3126/njst.v13i1.7392